2021
DOI: 10.1038/s41598-021-91602-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of peptidyl-prolyl cis–trans isomerases in Penicillium and their regulation by salt stress in a halotolerant P. oxalicum

Abstract: Peptidyl-prolyl cis–trans isomerases (PPIases) are the only class of enzymes capable of cis–trans isomerization of the prolyl peptide bond. The PPIases, comprising of different families viz., cyclophilins, FK506-binding proteins (FKBPs), parvulins and protein phosphatase 2A phosphatase activators (PTPAs), play essential roles in different cellular processes. Though PPIase gene families have been characterized in different organisms, information regarding these proteins is lacking in Penicillium species, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 92 publications
(82 reference statements)
2
14
0
Order By: Relevance
“…The expression of TaFKBP, TaPar and TaPTPA genes was analysed in response to heat stress to understand their likely role in thermotolerance of wheat seedlings. These results revealed that the expression of different TaFKBP and TaPar genes in wheat is modulated differentially by heat stress, which is in accordance with the earlier studies in O. sativa , Z. mays , M. domestica , and Penicillium ( Nigam et al., 2008 ; Yu et al., 2012 ; Dong et al., 2018 ; Waseem et al., 2018 ; Singh et al., 2021 ). For instance, the heat stress-induced increase in TaFKBP61-2-7D/TaFKBP62-1-7A/TaFKBP62-2-7B (Group 1) was also observed for their maize ortholog, ZmFKBP62a ( Yu et al., 2012 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The expression of TaFKBP, TaPar and TaPTPA genes was analysed in response to heat stress to understand their likely role in thermotolerance of wheat seedlings. These results revealed that the expression of different TaFKBP and TaPar genes in wheat is modulated differentially by heat stress, which is in accordance with the earlier studies in O. sativa , Z. mays , M. domestica , and Penicillium ( Nigam et al., 2008 ; Yu et al., 2012 ; Dong et al., 2018 ; Waseem et al., 2018 ; Singh et al., 2021 ). For instance, the heat stress-induced increase in TaFKBP61-2-7D/TaFKBP62-1-7A/TaFKBP62-2-7B (Group 1) was also observed for their maize ortholog, ZmFKBP62a ( Yu et al., 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…The FKBPs, parvulins and PTPAs are imperative for cis-trans isomerisation of the peptidyl-prolyl bonds, and several studies have revealed their essential role in diverse cellular processes ( Hanes et al., 1989 ; Luan et al., 1994 ; Lu et al., 1996 ; Janssens and Goris, 2001 ; Van Hoof and Goris, 2003 ; Gopalan et al., 2004 ; Meiri et al., 2010 ; Yu et al., 2012 ; Singh et al., 2021 ). The availability of whole genome sequences has enabled detailed in silico analysis and characterization of these gene families in different plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two hub genes of the HRR coexpression network match exactly with two of the genes found by GWAS, one of which was annotated for the enzyme peptidyl-prolyl cis-trans isomerase (PPIase). PPIases are associated with plant growth and development, and the related genes have previously been indicated as suitable candidates to increase the abiotic stress tolerance of plants for industrial processes and agricultural applications (Singh et al, 2021).…”
Section: Inferences Regarding Pine Growthmentioning
confidence: 99%